THOUGHTS ON COMMUNICATION IN THE SCIENTIFIC HERITAGE OF EASTERN THINKERS - Rakhimova Etibor Rustamovna; Askarova Dilafruz Jamaladdin qizi (American Journals, 2024)
In this article, the ideas of the views on communication in the scientific heritage of eastern thinkers are included. It was studied by them that priority is given to the issues of communication in the development of a person, and a lot of information about the issues of communication was presented.
Keywords: Communication, behavior, personality development, friendly attitude, rules of conduct, education, friendship.